Odpowiedź:
1.
a)
(6^4)^5 = 6^20
b)
6^4 * 6^5 = 6^9
c)
6^10/6^4 = 6^6
d)
6^5 : 6^4 = 6
e)
12^4 * 0,5^4 = (12 * 0,5)^4 = 6^4f)
12^5 : 2^5 = (12/2)^5 = 6^5
3.
a)
5² * 25 = 5² * 5² = 5^4
b)
125 * 5^6 = 5³ * 5^6 = 5^9
c)
125^8/5 = (5³)^8 : 5 = 5 ^24 : 5 = 5^23
d)
5^18 : 25^6 = 5^18 : (5²)^6 = 5^18 : 5^12 = 5^6
e)
(5^7 * 25)² = 5^14 * (5²)² = 5^14 * 5^4 = 5^18
f)
25^10 : 125^5 = (5²)^10 : (5³)^5 = 5^20 : 5^15 = 5^5
g)
(125²)^5 * 5 = [(5³)²]^5 * 5 = (5^6)^5 * 5 = 5^30 * 5 = 5^31
h)
(5^9/125)^4 = 5^36 : (5³)^4 = 5^36 : 5^12 = 5^24
Szczegółowe wyjaśnienie: